2007
DOI: 10.1051/alr:2008016
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation of fisheries sonar for monitoring schools of large pelagic fish: dependence of schooling behaviour on fish finding efficiency

Abstract: Multibeam omnidirectional sonars allow the monitoring of pelagic fish schools surrounding the platform and are currently used by fishermen. Multibeam processing methods offer improved abilities for raw data storage. For the detection of fish schools associated with drifting Fish Aggregating Devices (FADs), the Simrad SP90 sonar has been used. Digital systems have been developed for the acquisition and processing of volume backscattering echoes and position data. Sampling method was defined according to two mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
12

Year Published

2009
2009
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 29 publications
0
12
0
12
Order By: Relevance
“…Freon (1992) attempted an acoustic survey on a towed body, but was unsuccessful. Brehmer et al (2007) reported the first detection of flying fish aggregations by sonar, but it does not appear that this method was further developed. Studies focusing on tagging have provided general insight into movement and distribution patterns; however, it is difficult to implement on a large scale, and to examine population level abundance (Mulloney 1961, Lewis 1964, Oxenford 1994.…”
mentioning
confidence: 99%
“…Freon (1992) attempted an acoustic survey on a towed body, but was unsuccessful. Brehmer et al (2007) reported the first detection of flying fish aggregations by sonar, but it does not appear that this method was further developed. Studies focusing on tagging have provided general insight into movement and distribution patterns; however, it is difficult to implement on a large scale, and to examine population level abundance (Mulloney 1961, Lewis 1964, Oxenford 1994.…”
mentioning
confidence: 99%
“…Results obtained with ship-based (C1) multifrequency echosounders and omnidirectional sonar are detailed in Moreno et al (2007a); Brehmer et al (2007) and Trygonis et al (2016), respectively. Corresponding underwater SCUBA visual surveys are described in ).…”
Section: Results: Synthesis Of Methodological Approachesmentioning
confidence: 99%
“…However, in the scallop fishery, fishing has to be undertaken before CPUE can be determined, unlike other fisheries where sonar can be utilised (e.g. Brehmer et al 2007, Boswell et al 2008. Therefore, knowledge of prey distribution will necessarily be imperfect, limiting the numerical response.…”
Section: Discussionmentioning
confidence: 99%